Legal Protection for Creditors Against Guarantees Fiducia In The People's Business Credit Agreement (KUR) That Have Not Been Registered At The AHU KEMENKUMHAM (Case Study at PT. Bank Mandiri (Persero) Tbk Bombana Branch, Southeast Sulawesi) - Sam, Muhammad Iqbal; Ummu Adillah, Siti (TABELLIUS: Journal of Law, 2024)
Currently, many debtors are in default in taking credit with fiduciary collateral so that many assets are sold underhand and there are also debtors who are not responsible for the collateral, thus harming the creditor. The purpose of this study is to determine, review and analyze legal protection for creditors against fiduciary collateral in people's business credit agreements (KUR) that have not been registered with the AHU Kemekumham by PT. Bank Mandiri (Persero) Tbk Bombana Branch, Southeast Sulawesi and to determine, review and analyze the legal remedies owned by creditors if the debtor is in default. This study uses analytical descriptive specifications, the approach method used is a sociological legal approach, the types and sources of data in this study use primary data and secondary data. Secondary data includes primary legal materials, secondary legal materials and tertiary legal materials. The primary data collection method uses observation and interviews, the secondary data collection method uses document studies and literature studies. The data analysis method uses qualitative analysis methods. The results of the research and discussion show that legal protection for creditors against fiduciary guarantees in people's business credit agreements (KUR) that have not been registered with the AHU Kemenkumham if the debtor defaults, with the fiduciary guarantee law is the granting of preferential rights over his receivables and then according to the provisions of Article 21 paragraph (4) of the Fiduciary Law, the results of the transfer and/or bills that arise, by law become the object of a substitute fiduciary guarantee for the object of the transferred fiduciary guarantee. With the inclusion of the value of goods or objects that are used as objects of fiduciary guarantees, if the objects used as objects of fiduciary guarantees do not exist or are not available according to what is stated in the attachment, then the recipient of the fiduciary in this case the creditor can sue the party providing the fiduciary to fulfill his obligations, namely the amount of the guaranteed value as regulated in Article 6 of the Fiduciary Guarantee Law and the legal remedies owned by the creditor after the debtor defaults, which are carried out at PT. Bank Mandiri (Persero) Tbk Bombana Branch is the settlement of its dispute. First of all, this is done by giving a warning in the form of a reprimand, then continuing by giving a warning letter to the debtor, but if the debtor still does not comply, the creditor can take further action, namely through non-litigation and litigation methods.